2012
DOI: 10.4161/auto.19313
|View full text |Cite
|
Sign up to set email alerts
|

Dual functions of autophagy in the response of breast tumor cells to radiation

Abstract: In MCF-7 breast tumor cells, ionizing radiation promoted autophagy that was cytoprotective; pharmacological or genetic interference with autophagy induced by radiation resulted in growth suppression and/or cell killing (primarily by apoptosis). The hormonally active form of vitamin D, 1,25D 3 , also promoted autophagy in irradiated MCF-7 cells, sensitized the cells to radiation and suppressed the proliferative recovery that occurs after radiation alone. 1,25D 3 enhanced radiosensitivity and promoted autophagy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(55 citation statements)
references
References 48 publications
5
50
0
Order By: Relevance
“…Figure 4C confirms that recovery occurs after radiation-induced autophagy and senescence in both the HCT116 Ligase IV-proficient and Ligase IV-deficient cells. These findings are consistent with studies where proliferative recovery was observed after irradiation of MCF-7 breast tumor cells [16, 44]. …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Figure 4C confirms that recovery occurs after radiation-induced autophagy and senescence in both the HCT116 Ligase IV-proficient and Ligase IV-deficient cells. These findings are consistent with studies where proliferative recovery was observed after irradiation of MCF-7 breast tumor cells [16, 44]. …”
Section: Resultssupporting
confidence: 93%
“…We and others have reported that a primary response of tumor cells to radiation is autophagy [4447]. Figures 2A presents images of irradiated cells stained with acridine orange, which is indicative of autophagy while Figures 2B provides quantification of the extent of autophagy over a range of radiation doses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data revealed that calcitriol in combination with irradiation demonstrated an additive effect on the suppression of TIC-initiated spheroid formation, suggesting that these therapies likely target different pathways and provide a rationale for considering combining the two agents in clinical trials. Our findings are in agreement with previous reports documenting a sensitizing or additive effect of calcitriol with ionizing radiation (4749). It will be interesting to further explore the molecular effects of combined treatment with calcitriol and radiation and whether calcitriol can also enhance the anti-TIC effects of chemotherapy.…”
Section: Discussionsupporting
confidence: 94%
“…(1, 4, 40) Although numerous studies have shown a significant decrease in cell number with autophagy inhibition in combination with radiation or chemotherapy in breast cancer cell lines (41, 42) and in tumor xenografts;(4345) other studies show a limited or null effect. (46) While it makes sense that autophagy inhibition may be more beneficial when used with particular cancer therapies (e.g.…”
Section: Discussionmentioning
confidence: 99%